2022
DOI: 10.3390/ijerph19031435
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Psychosocial Functioning of Polish Nurses during COVID-19 Pandemic

Abstract: (1) The COVID-19 pandemic has significantly affected the psychological well-being of people around the world. The aim of this study was to assess the levels of psychological distress of nurses (anxiety, depression, stress, insomnia) in relation to sociodemographic variables and psychosocial variables: self-assessment of health, quarantine, psychological support, presence of chronic diseases and the Impact of Events Scale (IES-R). (2) A total of 207 nurses working with COVID-19 patients at the Independent Publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Similar conclusions based on the study were shown by Blekas et al, 2020 [ 68 ]; Di Tella et al, 2020 [ 58 ]; Işik et al, 2020 [ 69 ] and Steudte-Schmiedgen et al, 2020 [ 57 ]. Similar conclusions were presented in Polish research by Kosydar-Bochenek et al, 2021 [ 63 ]; Bidzan et al, 2020 [ 70 ] and Rachubińska et al, 2022 [ 71 ]. However, Qutishat et al, 2020 [ 72 ], in a study conducted among Jordanian nurses, and Alanazi et al, 2020 [ 73 ], in a literature review concerning emergency healthcare professionals during the COVID-19 pandemic, showed that men were characterized by a higher incidence of PTSD.…”
Section: Discussionsupporting
confidence: 87%
“…Similar conclusions based on the study were shown by Blekas et al, 2020 [ 68 ]; Di Tella et al, 2020 [ 58 ]; Işik et al, 2020 [ 69 ] and Steudte-Schmiedgen et al, 2020 [ 57 ]. Similar conclusions were presented in Polish research by Kosydar-Bochenek et al, 2021 [ 63 ]; Bidzan et al, 2020 [ 70 ] and Rachubińska et al, 2022 [ 71 ]. However, Qutishat et al, 2020 [ 72 ], in a study conducted among Jordanian nurses, and Alanazi et al, 2020 [ 73 ], in a literature review concerning emergency healthcare professionals during the COVID-19 pandemic, showed that men were characterized by a higher incidence of PTSD.…”
Section: Discussionsupporting
confidence: 87%
“…The consequence of long-term stress exposure is the risk of psychosomatic disorders. The intensification of this phenomenon was noted along with the COVID-19 pandemic, when a significant impact of stress on the mental health of nursing staff was observed [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that ethical issues can emerge in the workplace and healthcare providers following the crisis of the disease ( Patel et al, 2020 ). Mood swings and even suicide have been reported by nurses during the COVID-19 crisis ( Rachubinska, 2022 ). Anxiety, depression, sleep disorders, and stress have also been reported as psychological problems in the healthcare providers of COVID-19 patients ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%